Complicated Meningitis caused by a rare serotype of Haemophilus influenzae in Portugal - Calado, Rita (2011)
We report a case of meningitis due to Haemophilus influenzae serotype d strain in an infant. As far as we know, this is the first report of a serotype d strain, responsible for childhood invasive disease in Europe, demonstrating an emerging of H. influenzae non-b serotype, in the post-vaccination era.